The Paradox of Precision - Andre Fernando Oliveira (Orbital: The Electronic Journal of Chemistry, 2020)
This paper is about a typical mistake in the calculation of standard deviation of measurements in cases in which there are no differences among repetitious replicates. Some students believe the standard deviation in those case is equal to zero. So, this mistake leaves to a paradox: worse balance should show better results (i.e. standard deviation equal to zero). The solution of this simple, but important situation is shown.   DOI: http://dx.doi.org/10.17807/orbital.v12i2.1466